2023
DOI: 10.3390/cancers15061804
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Approach in Metastatic Renal Cell Carcinoma: A Literature Review

Abstract: The treatment of metastatic renal cell carcinoma has undergone considerable advances in the last two decades. Cytoreductive nephrectomy and metastasectomy retains a role in patients with a limited metastatic burden. The choice of optimal treatment regimen remains a matter of debate. The article summarises the current role of surgery in metastatic kidney cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The primary therapeutic goal is to achieve complete metastasectomy whenever it is surgically feasible. Undertaking any type of metastasectomy can enhance patient survival [39]. In our case, surgical intervention was absolutely indicated due to the development of an acute abdomen resulting from the perforation of an RCC metastasis.…”
Section: Surgical Management Of Rcc Metastasesmentioning
confidence: 86%
See 1 more Smart Citation
“…The primary therapeutic goal is to achieve complete metastasectomy whenever it is surgically feasible. Undertaking any type of metastasectomy can enhance patient survival [39]. In our case, surgical intervention was absolutely indicated due to the development of an acute abdomen resulting from the perforation of an RCC metastasis.…”
Section: Surgical Management Of Rcc Metastasesmentioning
confidence: 86%
“…However, in scenarios where targeted therapies do not yield dramatic results, surgical excision of isolated metastases continues to be a vital component in the treatment strategy for metastatic RCC [38]. Complete resection of the metastatic lesions is considered the most effective treatment for RCC metastases, and surgery remains the treatment of choice for localized metastatic RCC [39].…”
Section: Surgical Management Of Rcc Metastasesmentioning
confidence: 99%
“…They are often misdiagnosed as metastatic bone disease, especially in patients with a history of malignancy. Metastatic renal cell carcinoma (RCC) can have an aggressive course and can present with synchronous or metachronous metastasis in up to 20-30% of patients [ 1 ]. The 5-year overall survival of mRCC is about 20%.…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of the surgical management of mRCC, a meta-analysis by Zaid et al reported that a complete MST was associated with a reduced risk of all-cause mortality compared to incomplete surgical MST (pooled aHR 2.37, 95% CI 2.03–2.87, p < 0.001), with low heterogeneity (I 2 = 0%) [ 10 ]. On the other hand, a literature review by Matuszczak et al [ 11 ] reported that every group of patients with mRCC with a limited metastatic burden can benefit from a MST surgical procedure as long as their global health status allows them to undergo this procedure. Therefore, the optimal therapy may be tailored individually; above all, for younger patients with good clinical condition and low comorbidities, a surgical approach should always be considered to achieve a more likely “non-evidence of disease” (NED) status.…”
Section: Introductionmentioning
confidence: 99%